2007
DOI: 10.1002/hep.22039
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus urinaria ameliorates the severity of nutritional steatohepatitis both in vitro and in vivo

Abstract: Hepatic oxidative stress plays a critical role in metabolic forms of steatohepatitis. Phyllanthus urinaria, an herbal medicine, has been reported to have potential antioxidant properties. We tested the effects of P. urinaria on nutritional steatohepatitis both in vitro and in vivo. Immortalized normal hepatocytes (AML-12) or primary hepatocytes were exposed to control, the methionine-and-choline-deficient (MCD) culture medium, in the presence or absence of P. urinaria for 24 hours. Hepatocyte triglyceride, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…6,27 These pro-inflammatory regulators are mediated, at least in part, through oxidative stress. 27,28 In this study, PPARg activation significantly suppressed oxidative stress and blunted TNF-a and IL-6 gene expression in liver. Thus, the anti-inflammatory effects of PPARg may be partly related to inhibition of hepatic lipoperoxide and reductions in the mRNA expression levels of these regulators, in keeping with studies in other injury models that have shown that PPARg activation reduces proinflammatory cytokine production and inflammation.…”
Section: Role Of Pparc In Steatohepatitismentioning
confidence: 49%
“…6,27 These pro-inflammatory regulators are mediated, at least in part, through oxidative stress. 27,28 In this study, PPARg activation significantly suppressed oxidative stress and blunted TNF-a and IL-6 gene expression in liver. Thus, the anti-inflammatory effects of PPARg may be partly related to inhibition of hepatic lipoperoxide and reductions in the mRNA expression levels of these regulators, in keeping with studies in other injury models that have shown that PPARg activation reduces proinflammatory cytokine production and inflammation.…”
Section: Role Of Pparc In Steatohepatitismentioning
confidence: 49%
“…2A and B). Increases in hepatic Nrf2 expression was observed in conditions known to elevate CYP2E1, including the MCD diet (Shen et al, 2008;Gong et al, 2006). Thus, we examined whether ALA inhibition of CYP2E1 expression affects Nrf2 expression.…”
Section: Ala Inhibits Cyp2e1 Gene Expression In the Livers Of MCD Diementioning
confidence: 98%
“…Accumulating evidence suggests that CYP2E1, endoplasmic reticulum stress (ER), and redox sensitive inflammatory signaling pathways such as the MAP kinase and NFκB pathways are increased in human NASH as well as murine methionine-choline deficient (MCD) dietinduced steatohepatitis (Rahman et al, 2007;Puri et al, 2008;Shen et al, 2008). Recently, a CCl4-induced liver injury model showed that CYP2E1 is capable of inducing significant ER protein damage and stress (Lewis and Roberts, 2005;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Phyllanthus urinaria, a traditional medicinal plant, with a high amount of tannins and flavonoids, has also been documented to ameliorate the severity of steatohepatitis in in vitro and in vivo nutritional models. This effect seems to be attributed to the suppression of CYP2E1-mediated oxidative stress and JNK and NF-κB pathwaysmediated inflammatory response, in addition to the induction of fatty acid oxidation through CYP4A10 upregulation and the suppression of lipogenic transcription factor C/EBPβ [126]. Likewise, Ilex hainanensis Merr., whose major bioactive components are chlorogenic acid, kaempferol-7-O-β-Dglucoside and ilexgenin A [127], displays preventive effects on hepatic induced steatosis by alleviating insulin resistance and regulating lipid metabolism, inflammation and oxidative stress, through the regulation of PPARα and CYP2E1 expressions [128,129].…”
Section: Fig (2)mentioning
confidence: 97%